Vision Based Coin Separator Using Raspberry PI - Anupama R, Mohammed Farhan, Madan Gowda S, Naveen N, M. Vipul Ramesh (International Journal of Advanced Science and Technology, 2020)
Sorting is a ordering a list of objects in this two or more objects of same or different properties are fix in a systematic order. This is done either by human intervention or by using sensors and automating the process. For this problem we have proposed an automated system by using Raspberry pi as a primary component for determine the existence of coins, color and it’s radius. Thus allowing only that coins which are of wanted colors and radius to pass over conveyor belt. A linear actuator is started by pass a high signal when a coin of unwanted color is detected which push out the coins to unselect the undesired coin. This is carry out by using a PYTHON code which supports Raspberry Pi.